The role of trade liberalization and financial liberalization towards economic growth of brics - Wong, Joan Mei Tze (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Considering the growing emergence of BRICS economy, this study is crucial to policy makers who are interested to know how liberalization had impact on the economies of BRICS. This study examines the role of trade liberalization and financial liberalization towards the economic growth in Brazil, Russia, India, China and South Africa (BRICS) over nine year period starting from year 2003 to 2011. This study employs Levin, Lin and Chu (LLC) Panel unit root tests, Hausman Test, panel data estimation and Pedroni's cointegration test. Lastly, Granger causality test were conducted. The result shows that broad money supply (M2) has positive effect and significant on economic growth of BRICS. Domestic credit to Gross Domestic Product (GDP) ratio (DC) was found to be adversely affecting economic growth of BRICS.